URANG BANJAR: TOLAK-TARIK DEMOKRASI DAN KEBUDAYAANNYA - M. Rifqinizamy Karsayuda (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2017)
There are no general solutions to the problem of culturally divided countries. Every solutions will need to be costum tailored the features of each country. (Robert A Dahl)